Oncogenic Ras and B-Raf Proteins Positively Regulate Death Receptor 5 Expression through Co-activation of ERK and JNK Signaling - Oh, You-Take (American Society for Biochemistry and Molecular Biology, 2012)
Oncogenic mutations of ras and B-raf frequently occur in many cancer types and are critical for cell transformation and tumorigenesis. Death receptor 5 (DR5) is a cell surface pro-apoptotic death receptor for tumor necrosis factor-related apoptosis-inducing ligand and has been targeted in cancer therapy. The current study has demonstrated induction of DR5 expression by the oncogenic proteins Ras and B-Raf and revealed the underlying mechanisms. We demonstrated that both Ras and B-Raf induce DR5 expression by enforced expression of oncogenic Ras (e.g. H-Ras12V or K-Ras12V) or B-Raf (i.e. V600E) in cells and by analyzing gene expression array data generated from cancer cell lines and from human cancer tissues. This finding is further supported by our results that knockdown of endogenous K-Ras or B-Raf (V600E) reduced the expression of DR5. Importantly, we have elucidated that Ras induces DR5 expression through co-activation of ERK/RSK and JNK signaling pathways and subsequent cooperative effects among the transcriptional factors CHOP, Elk1, and c-Jun to enhance DR5 gene transcription. Moreover, we found that the majority of cancer cell lines highly sensitive to the DR5 agonistic antibody AMG655 have either Ras or B-Raf mutations. Our findings warrant further study on the biology of DR5 regulation by Ras and B-Raf, which may provide new insight into the biology of Ras and B-Raf, and on the potential impact of Ras or B-Raf mutations on the outcome of DR5-targeted cancer therapy.